2018
DOI: 10.1016/j.jconrel.2018.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, pharmacokinetic and pharmacodynamic analyses of amphiphilic cyclodextrin-based nanoparticles designed to enhance intestinal delivery of insulin

Abstract: Due to excellent efficacy, low toxicity, and well-defined selectivity, development of new injectable peptides is increasing. However, the translation of these drugs into products for effective oral delivery has been restricted due to poor oral bioavailability. Nanoparticle (NP) formulations have potential to overcome the barriers to oral peptide delivery through protecting the payload and increasing bioavailability. This study describes the rational design, optimization and evaluation of a cyclodextrin-based N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…We then placed samples upon a shaking table set to 100 r/min and set to run for a pre-specified time. 4 In addition, 400 μL of sample was collected from SGF or SIF at predetermined time points and placed into a quartz cell. The corresponding values for the spectrum were recorded at 20°C by the use of a Chirascan spectrophotometer (Chirascan, Applied Photophysics, Surrey, UK).…”
Section: Investigation Of the Stability Of Insulin Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…We then placed samples upon a shaking table set to 100 r/min and set to run for a pre-specified time. 4 In addition, 400 μL of sample was collected from SGF or SIF at predetermined time points and placed into a quartz cell. The corresponding values for the spectrum were recorded at 20°C by the use of a Chirascan spectrophotometer (Chirascan, Applied Photophysics, Surrey, UK).…”
Section: Investigation Of the Stability Of Insulin Nanoparticlesmentioning
confidence: 99%
“…Based upon determinations of the best stability of HA-DCDA-CS-r8-INS NPs in the preparation process, enzyme stability was further assessed by circular dichroism (CD). 4 CD spectrums for the insulin group were significantly changed in simulations of gastric fluid (SGF) treatments and demonstrated that the secondary structure was obviously destroyed (Figure 5B and C). Compared with the insulin solution, the degradation of insulin in the nanobased preparation was almost negligent.…”
Section: Enzyme Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…al. reported amphiphilic CD21 ‐based NPs for enhancing the intestinal delivery of insulin glulisine, a rapid‐acting insulin analogue for anti‐diabete. After encapsulating insulin glulisine, the obtained NPs shown average diameter of 109 nm and insulin glulisine loading of 10.2 %.…”
Section: Amphiphilic Cds For Drug Deliverymentioning
confidence: 99%
“…Percentage of the initial blood glucose levels following instilled to the jejunum by insulin glulisine solution, insulin glulisine NPs, and PBS, and subcutaneous administration of insulin glulisine solution. Reprinted with permission from Ref [53]. Copyright 2018 from Elsevier.…”
mentioning
confidence: 99%